2010
DOI: 10.3892/ol_00000108
|View full text |Cite
|
Sign up to set email alerts
|

p53R2 expression as a prognostic biomarker in early stage non-small cell lung cancer

Abstract: Abstract. p53R2 is a small subunit of ribonucleotide reductase (RR) which has 80% homology to hRRM2 and metastasissuppressing potential. Previous reports suggested that the expression of p53R2 is used as a prognostic factor and chemotherapy response indicator in several types of cancer. This study aimed to elucidate the association of p53R2 expression and the clinicopathological characteristics of early stage nonsmall cell lung cancer (NSCLC). Immunohistochemistry was conducted on a tissue array including 92 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In addition, high p53R2 expression is also a poor prognostic biomarker in non-small cell lung cancer [71] and squamous cell carcinoma [73]. However, some studies have indicated that high p53R2 leads to a better prognosis [74, 75]. Future studies will need to be done on larger patient cohorts to truly determine whether p53R2 expression predicts better or worse patient outcome.…”
Section: Nucleotide Metabolism In Cancermentioning
confidence: 99%
“…In addition, high p53R2 expression is also a poor prognostic biomarker in non-small cell lung cancer [71] and squamous cell carcinoma [73]. However, some studies have indicated that high p53R2 leads to a better prognosis [74, 75]. Future studies will need to be done on larger patient cohorts to truly determine whether p53R2 expression predicts better or worse patient outcome.…”
Section: Nucleotide Metabolism In Cancermentioning
confidence: 99%
“…The RRM2 can be substituted by p53-inducible small subunit RRM2B (ribonucleotide reductase regulatory TP53 inducible subunit M2B; also known as p53R2) that regulates the synthesis of deoxyribonucleotide triphosphates (dNTPs) required for DNA damage repair [28]. Unlike RRM1 and RRM2, p53R2 suppresses invasiveness and its expression is usually associated with a better prognosis for cancer patients [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Possibly elevated RNR subunit expression may be a reflection of increased numbers of cancer cells in S phase. In early stage non small cell lung cancer, Hsu et al [ 17 , 18 ] found RRM2 correlated positively with tumor grade and patients with RRM2- and RRM2b+ tumors had better outcomes. In their study RRM2b was a better predictor for both recurrence and survival than RRM2.…”
Section: Introductionmentioning
confidence: 99%